Ballet Gesture Recognition and Evaluation System (Posé Ballet): System Thinking, Design Thinking, and Dynamic Improvement in Three Versions - Apirath Limmanee; Peeraphon Sayyot (My University, 2023)
This paper elaborates the design and implementation of “Posé Ballet,” the ballet gesture recognition and evaluation system using MS Kinect camera. “Posé Ballet” has gone through continual development which can be divided into three phases according to requirements from three different user groups. These three groups are ballet students, ballet teachers and dancers, as well as beginners and laypersons. After the technical side of the system is explained, we describe our “design thinking” concepts. With these concepts, our new and improved third-version software as well as GUI are developed to serve the visitors at Bangkok Art and Culture Centre (BACC). At the end, some results and feedback are collected. These give us insight on how to improve our system further toward the goal of being standardized or commercialized.
Keywords: Human Motion and Animation; Diversity and Impact of Dance; Educational Games and Gamification